A survey on quantum positioning system. (4th July 2021) - Duan, Shiqi; Cong, Shuang; Song, Yuanyuan
ABSTRACT: The quantum positioning system (QPS) takes advantage of the entanglement property of the quantum system itself, and it is possible to breakthrough the limitation of the positioning accuracy due to signal bandwidth and power limitation in classical radio-based global positioning system (GPS), and improve the positioning performance. In this paper, a comprehensive survey of the research status of QPS and its several key components are presented, including the quantum entanglement states preparation, the quantum satellite technique, the optical signal acquisition, tracking and pointing (ATP) system, and the quantum positioning and clock synchronization technique. We also discuss the current challenges and future research directions at the end of the paper.